Recent advances in cannabidiol (CBD) extraction: a review of potential eco-friendly solvents and advanced technologies - Saranya Selvaraj; Nazeefa Nawfer; K.V. Surangi Dharmawansa; Ali Ali Redha; H.P. Vasantha Rupasinghe (Green Analytical Chemistry)
Cannabinoids, particularly cannabidiol (CBD), have been gaining attention for their numerous potential health benefits and are employed in various industries. However, there are unresolved challenges in CBD extraction including low yields, impurity issues, and environmental concerns, suggesting the requirement for green methods. Hence, our review objectives are to assess the efficacy, and the impact of novel solvents used for CBD extraction, considering green and sustainable techniques. The traditional extraction methods such as maceration and Soxhlet extraction used for CBD extraction have limitations such as low efficiency, long extraction times, high energy consumption, and substantial CO₂ emissions, raising environmental concerns. Emerging green extraction techniques, such as supercritical fluid extraction, deep eutectic solvents, and microwave-assisted extraction, offer promising alternatives by reducing solvent use, minimizing processing time, and enhancing extraction yields. Supercritical CO2 extraction, utilizing supercritical fluids' unique properties offers efficient and safe CBD extraction. Emerging green solvents such as ionic solvents and deep eutectic solvents provide promising alternatives for CBD extraction due to their properties such as no or low toxicity compared to the traditionally used solvents. Pressurized liquid extraction, such as subcritical water extraction, and techniques like microwave-assisted and ultrasonic-assisted extraction provide rapid and efficient alternatives for CBD extraction. To fulfill the growing demand for CBD extracts, future research can aim at developing efficient and sustainable extraction techniques while reducing the potential degradation of CBD, removing impurities produced during extraction, and considering concepts of sustainability and the One Health approach.